Interpretive phenomenological analysis (IPA) of organisational factors related to maintenance reliability in a petroleum production workplace - Antonovsky, A.; Pollock, C.; Straker, Leon (Human Factors and Ergonomics Society of Australia Inc. (HFESA), 2013)
Aim: To understand the influence of organisational factors on workplace effectiveness in petroleum processing operations based on perceptions of maintenance technicians. Background: Numerous engineering measures exist for determining the effectiveness of maintenance and reliability of equipment. However, technical measures may not provide sufficient insight into the causes of poor reliability. It is therefore worth improving our understanding of both the human factors specific to this domain, as well as the factors that may influence worker effectiveness in industrial workplaces. Method: Maintenance personnel completed a survey as part of a larger study of maintenance reliability. The survey included the request: "Please write any comments you have on what helps or gets in the way of maintenance work at [target organisation]." These comments were analysed to extract sub-themes using an Interpretive Phenomenological Analysis (IPA) methodology. Constructs common to these sub-themes were grouped into a smaller number of shared themes and these were used to identify super-ordinate themes. For comparison, a measure was developed to determine the reliability of the facility on which the participant worked. Results: 178 participants completed the survey and 101 (55.6%) submitted a written comment. A total of 57 distinct sub-themes were extracted from the comments, and 12 themes were identified within these sub-themes. The themes were grouped into four super-ordinate themes: 1) Communication and access to information, 2) Efficiency of current work systems, 3) Need for better workgroup support, and 4) Management impacts on the workplace. Differences were identified in the frequency of these overarching themes based on facility reliability level. Conclusion: Comments related to Efficiency of work systems were more frequent from the higher reliability facilities. These comments reflected confidence in the performance.